Estudio de la residualidad de herbicidas preemergentes en el cultivo de arroz en la zona de Babahoyo - Andrade Molina, Ana Priscila (2013)
The present investigation work was carried out in dry time, in the lands of Mr. Caesar's property Andrade, located in the road Chilintomo - Babahoyo, canton Babahoyo, county of The Ríos; with coordinated geographical 010 56'de South latitude and 800 36' of longitude West, altitude of 60 m.s.n.m. Certified seed of the variety INIAP was used 15 whose treatments were constituted by the herbicides Gamit (1.8 L/ha), Prowl (4,0 L/ha), Bolero (4,0 L/ha), Ronstar (1,5 L/ha), Machete (4,0 L/ha) and the mechanical witness with three manual deshierbas. He/she was carried out the experimental design of Blocks Totally at random with six treatments and three repetitions. The comparisons of the stockings were made with the test of multiple range from Duncan to 5% of probability. They were carried out all the practices and agricultural works that he/she needed the cultivation for their normal development as floor analysis, preparation of the land, siembra, control of overgrowths, watering, fertilization, control fitosanitario, harvests. To evaluate in correct form the effects of the treatments herbicides, in each parcel toxicity index was evaluated to the 7 and 14 days after the application, control of overgrowths to the 20 and 40 days, macollos number for square meter, number of spikes for square meter, number of days to floración, number of days to maturation, plant height, panícula longitude, number of grains for spike, yield of the cultivation and economic analysis.